Krishi Kund for agroecological transition of degraded lands: microsite for improved production and ecosystem services [Abstract only] - Malaiappan, Sudharsan; Kumar, Gopal; Sikka, Alok (BOKU University of Natural Resources and Life Sciences, 2024)
Decades of rampant land degradation have rendered many areas unsuitable for cultivation. In Madhya Pradesh, India, land degradation along with difficult terrain, and poor soil conditions make significant portions of land unfit for cultivation leading to the migration of tribal communities. These degraded or sporadically cultivated lands are caught in a vicious cycle leading to further degradation.